Dampak Partisipasi Program Kelompok Usaha Bersama (KUBE) Terhadap Kesejahteraan Penerima Program - Ar Kamardi Indra; Firwan Tan; Maryanti Maryanti (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2022)
Based on the Preamble of the 1945 Constitution, the State has an obligation to realize the welfare of the people. The state has issued various programs to improve people's welfare, one of which is micro-credit which has various forms of distribution. One form of microcredit is Kelompok Usaha Bersama (KUBE). Propensity Score Matching (PSM) is used to divide the control group and the program recipient group so that they have the same average score therefore the impact on the welfare of program recipients can be calculated. The results of this study were the recipients of the KUBE program experienced a decrease in welfare in the indicators of per capita expenditure, education, health, housing, and other social activities as well as an increase in the duration of work in the employment indicator.